Determinant factors affecting e-financial reporting in Malaysia - Ali Khan, Mohd. Noor Azli (2012)
This research attempts to investigate the current state of the level of internet financial reporting (IFR) in Bursa Malaysia. The items in the dimensions are based on the perspective of overall preparers and users.